Statistical characterization of equatorial plasma bubbles over East Africa - Abiriga, Faustine; Amabayo, Emirant B.; Jurua, Edward; Cilliers, Pierre J. (Journal of Atmospheric and Solar-Terrestrial Physics, 2020)
Bubble-like structures that grow in the post-sunset F-region of the equatorial ionosphere have continued to raise concern and research interest among scientists. These structures, commonly referred to as Equatorial Plasma Bubbles (EPBs), have depleted electron densities surrounded by a denser plasma. When Trans-ionospheric radio signals interact with the EPBs, the signals get attenuated and scattered due to reflective, refractive and diffractive scattering effects of the EPBs on the signals. This compromises the quality, accuracy and reliability of information obtained from Global Navigation Satellite Systems (GNSS). In this study, we have used the Global Positioning System (GPS) slant Total Electron Content (sTEC) data to identify and characterize EPBs. This data was obtained from International GNSS Service (IGS) receivers located within the East African region identified by the geographic latitudes (􀀀 7 to þ7)oN and geographic longitudes (þ29 to þ41)oE. Identification of the EPBs was based on the de-trended curve of the sTEC-time series while their characterization was based on the standard deviation of their depletion depths from their calculated mean depletion depth. On this basis, three categories of EPBs were obtained. Results obtained show that the occurrence of the different categories of EPBs have got a seasonal pattern.
Keywords: Equatorial plasma bubbles; Global navigation satellite systems; Ionospheric irregularities; Slant total electron content